Effective treatment and good cosmetic results in the treatment of pilonidal sinus disease; Comparison of four surgical methods (Annals of Medical Research, 2021)
Aim: In the treatment of pilonidal sinus disease (PSD), the patient wishes to be able to get rid of the disease quickly and effectively with the ideal treatment, which not only improves the patient's satisfaction with the best cosmetic result but also has a low recurrence rate. The aim of this study is to demonstrate that the gluteal sliding transposition (GST) method is more advantageous and preferred by patients in terms of better cosmetic results and lower loss with lower recurrence and complication rates.Materials and Methods: Between 2008 and 2017, patients who were operated for PSD were retrospectively reviewed using hospital digital records. Four groups of patients were included in the study: those who underwent excision and secondary healing (ESH), excision and primary repair (EPR), GST, and Limberg flap transposition (LFT). The groups were compared based on time of hospitalization, time of healing, time of labor loss, infection, hematoma, seroma and wound dehiscence, flap necrosis, paresthesia, recurrence and aesthetic satisfaction.Results: Between 2008 and 2017, 1526 patients underwent PSD surgery in the hospital. Of the patients, 276 were female and 1250 were male, and their median age was 21.3 (16-45) years. The mean follow-up was 24 months (6-120 months). The longest mean operation time (46.04 ± 9.1 min) was found in LFT patients. The longest time of healing was in the ESH group (49.62 ± 12.7 days) (p0.05). Although there was no significant difference between GST and LFT in terms of healing time, the time of healing was shorter in GST than in ESH and EPR methods (18.72 ± 7.72 days) (p0.05). The shortest loss of labor was observed in EPR (13.53 ± 2.02 days) (p0.05). The hematoma, seroma and the wound opening were more significant with the EPR method than other methods (p0.05). While the aesthetic satisfaction was expected to be greater for the reconstructive procedure of LFT, the results showed that aesthetic satisfaction was found to be better with the GST method (p0.05). In terms of recurrence, GST was also found to be the most advantageous method (4.4%) (p0.05).Conclusion: The GST method provides lower hospitalization and complication rates, similar to the ESH, and quicker wound healing with lower recurrences, as in LFT. In addition, GST has better aesthetic satisfaction than LFT.
Keywords: Pilonidal sinus disease; surgery; gluteal sliding transposition